A Comparative Study on a Virtual 3d Context on the Video Collaborative Virtual Environment in Celebrity Quotes, Dream House and Desert Survival Game: Exploring the Impact of Collaborative Virtual Environments on Face-to-Face Collaboration (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Collaborative Virtual Environment (CVE) ideas have been utilized in numerous devices in the past couple of years. Use of technology range that is from army fighting simulations to different civilian industrial uses the goal of the analysis is actually analyzing the outcome of 3 dimensional (3D) virtual environment and augmented reality apps. The overarching goal of the tests discussed in this specific thesis was investigating whether individuals collaborating in video CVEs feel and behave much more similarly to being face-to-face compared to individuals collaborating through regular video conferencing tools.